The Effect of Growth and Development Stimulation on the Development of Infants with Cancer Aged 1–3 Years (Toddlers) - Fifit Kustiani Kustiani; Wenny Rahmawati Rahmawati; Dinda Oktia Maghfiroh Maghfiroh (Media Husada Journal of Midwifery Science, 2025)
Abstract The growth and development of children aged 1–3 years (toddlers) suffering from cancer often face obstacles due to the impact of the disease and the therapies undergone, such as chemotherapy and radiation. Developmental delays can affect children's motor, cognitive, language, and social aspects. Providing growth and development stimulation is one intervention that can help optimize child development under these conditions. This study aims to analyze the effect of growth and development stimulation on the development of toddlers with cancer. This study used a pre-experimental method with a One-Group Pre-Post Test Design approach. The sampling technique used was non-probability sampling with purposive sampling. Data collection was conducted through observations of children's development before and after the intervention of growth and development stimulation. Data analysis was performed using the Wilcoxon Sign Rank Test to examine differences in development before and after stimulation. The statistical test results showed a p-value of 0.000, indicating a significant effect of growth and development stimulation on the development of children aged 1–3 years with cancer. This study concludes that growth and development stimulation plays a crucial role in improving the development of children experiencing delays due to cancer. Therefore, it is recommended that healthcare professionals and parents provide appropriate and continuous stimulation to support optimal child growth and development. Abstrak Pertumbuhan dan perkembangan anak usia 1–3 tahun (batita) yang menderita kanker sering mengalami hambatan akibat dampak penyakit dan terapi yang dijalani, seperti kemoterapi dan radiasi. Keterlambatan perkembangan dapat berpengaruh pada aspek motorik, kognitif, bahasa, dan sosial anak. Pemberian stimulasi tumbuh kembang menjadi salah satu intervensi yang dapat membantu mengoptimalkan perkembangan anak dalam kondisi tersebut. Penelitian ini bertujuan untuk menganalisis pengaruh pemberian stimulasi tumbuh kembang terhadap perkembangan batita yang menderita kanker. Penelitian ini menggunakan metode pra-eksperimental dengan pendekatan One Group Pre-Post Test Design. Teknik sampling yang digunakan adalah non-probability sampling dengan jenis purposive sampling. Pengumpulan data dilakukan dengan observasi perkembangan anak sebelum dan sesudah intervensi stimulasi tumbuh kembang. Sampel yang digunakan pada penelitian ini adalah 30 batita yang menderita kanker di Ruang Tondano RSUD dr. Saiful Anwar Malang. Analisis data menggunakan Wilcoxon Sign Rank Test untuk menguji perbedaan perkembangan sebelum dan sesudah pemberian stimulasi. Hasil uji statistik menunjukkan nilai p = 0,000 yang berarti terdapat pengaruh yang signifikan dari pemberian stimulasi tumbuh kembang terhadap perkembangan anak usia 1–3 tahun yang menderita kanker. Dari penelitian ini dapat disimpulkan penelitian bahwa stimulasi tumbuh kembang memiliki peran penting dalam membantu meningkatkan perkembangan anak yang mengalami keterlambatan akibat kanker, terutama yang menjalani kemoterapi. Oleh karena itu, disarankan agar tenaga kesehatan dan orang tua memberikan stimulasi yang sesuai dan berkelanjutan guna mendukung pertumbuhan serta perkembangan anak dalam kondisi yang optimal.